Dietary Recommendations for the Management of Gastrointestinal Symptoms in Patients Treated with GLP-1 Receptor Agonist - Gentinetta S; Sottotetti F; Manuelli M; Cena H (Diabetes, Metabolic Syndrome and Obesity)
Silvia Gentinetta,1,* Francesca Sottotetti,2,* Matteo Manuelli,3 Hellas Cena2,3 1Novo Nordisk Italia SpA, Roma, Italy; 2Laboratory of Dietetics and Clinical Nutrition, Department of Public Health, Experimental and Forensic Medicine, University of Pavia, Pavia, Italy; 3Clinical Nutrition Unit, Istituti Clinici Scientifici Maugeri IRCCS, Pavia, Italy*These authors contributed equally to this workCorrespondence: Francesca Sottotetti, Laboratory of Dietetics and Clinical Nutrition, Department of Public Health, Experimental and Forensic Medicine, University of Pavia, Pavia, Italy, Email francesca.sottotetti@unipv.itAbstract: GLP-1 receptor agonist (GLP-1RA) have been developed to address the global burden of obesity and are renowned for their safety and efficacy. These medications influence hunger and satiety, reducing energy intake and promoting weight loss. Despite their benefits, GLP-1RAmay cause a slowed gastric emptying, leading to gastrointestinal symptoms. This study examines how food properties and meal composition affect these symptoms. Dietary recommendations are provided, particularly for evening meals, focusing on how different foods and nutrients can influence the rate of gastric emptying, to improve patient compliance and prevent interruption in weight loss.Keywords: obesity, GLP-1 receptor agonist, gastric emptying, nausea, food viscosity